Composite materials containing construction and polymer waste - A. A. Baruzdin; L. V. Zakrevskaya (Vestnik MGSU)
Introduction. This research is a consolidated study of recycling in the construction industry. The recycling of construction and polymer industry waste is analyzed. Currently used methods and technologies of cross-linked polyethylene waste recycling are presented.Materials and methods. The research and testing equipment with high reproducibility of results is used. Properties of manufactured specimens of materials were determined by standard methods. Methods of X-ray phase analysis, optical and scanning electron microscopy were used to study the structure of materials.Results. Compositions of composite materials with density from 1,750 to 2,000 kg/m3 and compressive strength from 20 to 40 MPa have been developed. Compositions included Portland cement, waste of cross-linked polyethylene and ceramic bricks, polycarboxylate plasticizer, silica filler and calcium chloride solution. The possibility of using floured broken brick as a partial replacement of cement and crushed cross-linked polyethylene as an aggregate is investigated. The microstructure of the obtained composite materials was studied and it was concluded that cross-linked polyethylene aggregate is reinforce a homogeneous matrix, which is a product of the interaction of cement, brick powder and silica filler. During the hardening of matrix strong crystal structure consisting of hydrosilicates and calcium and quartz carbonates is formed.Conclusions. The obtained results can be used in the production of building composite materials based on recycling of ceramic brick waste and cross-linked polyethylene. Due to the fact that the cost of the presented waste is much lower than the cost of Portland cement and traditional aggregates (by about 25 %), and their recycling is accompanied by the reduction of negative impact on the environment, composites based on them have good prospects for implementation in construction practice.